Analysis of Interest in Learning Physical Education in Students MIN 1 Bengkulu City - Dery, Liqa Avloren (Indonesian Journal of Sport, Health and Physical Education Science, 2023)
This study aims to determine student interest in learning physical education at MIN 1 Bengkulu City. The method used is quantitative descriptive research in the form of a survey method. The subjects of this study were class Va students who were recorded as 38 students. The instrument used is a questionnaire. The analysis technique used is pouring the frequency into percentage form. The highest frequency obtained is that students' interest in learning physical education is in the moderate category, totaling 11 students or with a percentage of 28.94%. The results obtained then were in the very high category, totaling 10 students or with a percentage of 26.31%, the low category amounted to 10 students or with a percentage of 26.31%, and the last result obtained was in the very low category totaling 7 students or with a percentage of 18.42%.